Factors associated with disapproval of female genital mutilation among schoolgirls in the Borena and Jimma zones of Ethiopia - Henok Mulatu Teferi; Gizachew Balew Jembere; Siyoum Enqubahiri; Teferi Kebede Nurgi; Amina Kanpise Arero; Biruk Bogale Wolde; Wondimu Chifra Tolera; Addisalem Titiyos; Pontea Afzalirad; Kathryn A O’ Connell; Danielle Garfinkel (International Journal of Adolescence and Youth)
This research assessed the prevalence of and factors associated with disapproval of female genital mutilation/cutting (FGM/C) in the Borena and Jimma zones of Ethiopia using a cross-sectional study among 679 schoolgirls aged 15–24 years old. Results show an overall 80.7% prevalence of attitudes against FGM/C. Individuals from Borena [AOR = 1.76;95% CI: 1.03,2.98] and Christian religion followers compared to Muslims [AOR = 2.12; 95% CI: 1.07, 4.20] had higher odds of expressing attitudes against FGM/C. Those participants who agree to the statement ‘a woman or man can suggest using a condom’ [AOR = 2.79; 95% CI:1.73, 4.52] and ‘it is okay for a woman to say no to sexual intercourse’ [AOR = 2.46; 95% CI:1.31, 4.61] were also significantly more likely to oppose FGM/C. Through this study, we have identified the influence of geography, culture, and religion in shaping attitudes towards FGM and noted the missed opportunity of using school-based interventions to tackle this issue.